Caracterização petrográfica das rochas vulcânicas da formação mosquito-bacia do Parnaíba-Fortaleza dos Nogueira e Estrito (MA) - OLIVEIRA, Suzana Chaves de (2019)
Mosquito Formation consists of basalt flows with interbedded sandstone, tholeiitic composition and correlated with magmatism Penatecaua Basins Solimões and Amazonas. The basalts have dark colored, rarely with green tones, aphanitic and are filled by zeolites have tonsils, these rocks were older and had been shed during the deposition of wind Sambaíba Training. Literature has been interpreted as reflecting the opening of the Atlantic. These basalts have ages ranging between 110 and 215 Ma and may be associated with two main magmatic pulses, exhibit age-Triassic swear.